Single cell analysis via mass cytometry of spontaneous intestinal perforation reveals alterations in small intestinal innate and adaptive mucosal immunity - Olaloye, Oluwabunmi; Eke, Chino; Jolteus, Abigail; Konnikova, Liza (Frontiers in Immunology, 2023)
Introduction Spontaneous intestinal perforation (SIP) is a poorly understood severe gastrointestinal complications of prematurity which is poorly understood. Extremely premature infants born prior to 28 weeks’ gestation develop a localized perforation of the terminal ileum during the first week of life and therapy involves surgery and cessation of enteral feeds. Little is known regardj g the impact of mucosal immune dysfunction on disease pathogenesis. Methods We performed mass cytometry time of flight (CyTOF) of small intestinal mucosa of patients with SIP (Gestational age (GA) 24 – 27 weeks, n=8) compared to patients who had surgery for non-SIP conditions (neonatal (GA >36 weeks, n=5 ) and fetal intestine from elective terminations (GA 18-21 weeks, n=4). CyTOF analysis after stimulation of T cells with PMA/Ionomycin was also performed. Results We noted changes in innate and adaptive mucosal immunity in SIP. SIP mucosa had an expansion of ckit+ neutrophils, an influx of naïve CD4 and CD8 T cells and a reduction of effector memory T cells. SIP T cells were characterized by reduced CCR6 and CXCR3 expression and increased interferon gamma expression after stimulation. Discussion These findings suggest that previously unrecognized immune dysregulation is associated with SIP and should be explored in future studies.